An Empirical Assessment of Participation and Decision Making by Rural Women in Agriculture and Livestock Activities - Chaudhary, Rashmi; Janjhua, Yasmin; Avineet; Kumar, Krishan (International Journal of Economic Plants, 2020)
Women make essential contributions to agriculture and rural economic activities in all developing countries. Even though women contribute 60 to 80% of the labour in agriculture and animal husbandry, their involvement in selection of suitable crops and adoption of innovative and good management practices is very low. The study reported that sampled women respondents have shown participation in all the selected agriculture and livestock activities excluding marketing and financial management. The study put forth that very less households witness female participation in agriculture and livestock activities related decision making. Some of the important reasons for their subdued role in decision making in agricultural production could be lack of awareness about new opportunities and modern technologies, inadequate facilities for training and capacity building and poor access to extension workers for consultation whenever needed.